1995
DOI: 10.1002/jms.1190300911
|View full text |Cite
|
Sign up to set email alerts
|

Determination of both linkage position and anomeric configuration in underivatized glucopyranosyl disaccharides by electrospray mass spectrometry

Abstract: Negativeion electrospray mass spectrometry was used to determine directly both glycosidic linkage position and anomeric configuration in the complete glucopyranosyl disaccharide series without the need for derivatization or tandem mass analysis. A series of empirical criteria were developed which first differentiate between the linkage positions and then the anomeric configurations using selected diagnostic peaks and their relative intensities. The use of standard mass spectral library searching methods for st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
102
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 39 publications
5
102
1
1
Order By: Relevance
“…For nonderivatized oligosaccharides, linkage-specific cross-ring fragments are observed, too; this has been shown for small oligosaccharides accessible by fast atom bombardment (FAB), laserdesorption/ionization (LDI) or electrospray/ionization (ESI); cross-ring fragment ions are found both in the positive [37][38][39][40][41] and negative ion mode [42,43] and are believed to originate from a ring opening at the reducing end sugar in a pericyclic hydrogen rearrangement of the retro-aldol reaction type [37] (see Scheme 1). This may be followed by cleavages after enolization, resulting in loss of linkage-specific neutral fragments.…”
mentioning
confidence: 95%
“…For nonderivatized oligosaccharides, linkage-specific cross-ring fragments are observed, too; this has been shown for small oligosaccharides accessible by fast atom bombardment (FAB), laserdesorption/ionization (LDI) or electrospray/ionization (ESI); cross-ring fragment ions are found both in the positive [37][38][39][40][41] and negative ion mode [42,43] and are believed to originate from a ring opening at the reducing end sugar in a pericyclic hydrogen rearrangement of the retro-aldol reaction type [37] (see Scheme 1). This may be followed by cleavages after enolization, resulting in loss of linkage-specific neutral fragments.…”
mentioning
confidence: 95%
“…The soft mass spectrometry ionization techniques such as fast atom bombardment (FAB) [12][13][14][15][16], liquid secondary ionization mass spectrometry (LSIMS) [17,18], along with matrix-assisted laser desorption ionization (MALDI) [19 -23], and electrospray ionization (ESI) [24 -28] have gained attention as approaches to investigate underivatized oligosaccharides. Collision-induced dissociation (CID) offers the possibility to assign details of carbohydrate structure such as sugar sequence for linear oligosaccharides [12], linkage position [12,[15][16][17]29], and differentiation of anomers [25,30]. In addition to analyzing protonated or deprotonated molecular ions of saccharides in CID, alkali metal adduct ions have been used to promote fragmentation of ligand-carbohydrate complexes.…”
mentioning
confidence: 99%
“…It has been shown that the relative abundances of these ions can be correlated to the linkage position, and in some cases, the anomeric configuration and stereochemistry of each monosaccharide. For example, CID spectra of deprotonated di-and oligosaccharide alkoxy anions in the negative ion mode showed distinguishable fragmentation patterns for each linkage position, which was successfully applied to di-, tri-, and hexasaccharides [14][15][16][17]. Negative ion adducts [18,19] and positive adducts [20,21] of deprotonated di-and oligosaccharides have also enabled linkage positions to be determined, both in the negative and positive ion modes, and linkage sites can be established for neutral disaccharides as positive ion adducts of lithium or sodium ions or as protonated adducts [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Negative ion adducts [18,19] and positive adducts [20,21] of deprotonated di-and oligosaccharides have also enabled linkage positions to be determined, both in the negative and positive ion modes, and linkage sites can be established for neutral disaccharides as positive ion adducts of lithium or sodium ions or as protonated adducts [22][23][24][25][26][27]. Determination of anomeric configuration has been demonstrated for underivatized disaccharides in the negative ion mode [15,17,18], for derivatized 1-4-and 1-6-linked disaccharides [28], and in the positive ion mode with alkali metals [22][23][24][25][26][27] and lead cationization [20]. Prior knowledge such as linkage position, ring form, and stereochemistry [15,17,18,20,[22][23][24][25][26][27][28], however, was typically required to assign anomeric configuration, which was difficult to apply to larger oligosaccharide systems [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation